Thoracic Scoliosis in Patients with Primary Spontaneous Pneumothorax - Lee, Yeiwon (Korean J Thorac Cardiovasc Surg, 2018)
BACKGROUND: Primary spontaneous pneumothorax (PSP) affects patients without clinically apparent lung disorder found in tall and thin young male. Scoliosis refers to curves exceeding 10° Cobb angle observed through chest X-ray and affects 2% to 4% of adolescents. Both conditions are commonly encountered in primary health care setting. The aim of this study is to access the correlation of thoracic scoliosis and PSP in adolescent. METHODS: A retrospective analysis was conducted for patients diagnosed for PSP in Konyang University Hospital between January 2010 and March 2017. Chest X-rays of 222 patients and 155 normal control (NC) cases were reviewed to measure the Cobb angle. Greater than 10° of Cobb angle is diagnosed as scoliosis. RESULTS: Scoliosis in patient with PSP has higher incidence than that of NC group (p<0.001). Median value of Cobb angle is 12.9° in PSP group and 14.7° in NC group. Directional relationship between scoliosis and pneumothorax in PSP group is also observed; 40.5% cases are ipsilateral and 59.5% are contralateral. CONCLUSION: PSP patients tend to have thoracic scoliosis more commonly compared with normal healthy adolescent. Scoliosis may contribute to heterogeneity of alveolar pressure which exacerbates subpleural bleb formation that can cause pneumothorax. The causal relationship is unclear and further studies are needed in the future.